Delivering on the Promise of Pro-Poor Growth: Insights and lessons from country experiences - Besley, Timothy; Cord, Louise J. (Basingstoke [England] ; New York : Palgrave Macmillan ; Washington DC : World Bank, 2007)
Examining the relationship between growth and poverty reduction among eight countries in the 1990s and early 2000s, this volume provides important lessons about what has and has not worked in these countries to increase the participation of poor households in growth.
Includes bibliographical references and index.
rpm 21/09/2016
Loans
Keywords: Economic development; Developing countries -- Economic conditions -- 20th century; Poverty; Poverty -- Developing countries -- Case studies